Intellectual Property Rights vs. access to medicines : the impact on the CSR strategy of pharmaceutical companies : the case of GlaxoSmithKline - Torres, Rita Fonseca Santos Monteiro (2013)
The aim of this dissertation is to study how Corporate Social Responsibility (CSR) is integrated in companies, with a special focus on the pharmaceutical industry. The problem statement relies on understanding how has the tension between the accessibility of essential medicines in developing countries and Intellectual Property Rights (IPRs) influenced the CSR strategy of multinational companies in the pharmaceutical industry over the last years. In order to act in accordance with this objective, a teaching case was developed, based on GlaxoSmithKline (GSK), a British multinational pharmaceutical that is the world’s second largest pharmaceutical company and world leader in the provision of drugs to treat the three most critical diseases in the developing world: HIV/AIDS, malaria and tuberculosis. GSK was the first company from the industry to approach the access to medicines issue as a strategic consideration, by incorporating it not only in its CSR strategy but also in the company’s overall strategy. The challenge faced translates how CSR practices, when adopted strategically, can simultaneously create economic and social value.